2020
DOI: 10.1111/sjop.12694
|View full text |Cite
|
Sign up to set email alerts
|

Personality and psychopathology heterogeneity in MMPI‐2 and health‐related features in fibromyalgia patients

Abstract: Personality and psychopathology heterogeneity in MMPI-2 and health-related features in fibromyalgia patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…These observations are relevant in view of the literature linking neuroticism to severe FM symptoms (including pain), pain-related catastrophizing and pain-related anxiety, and worse clinical and healthrelated outcomes (Bucourt et al, 2017;Kadimpati et al, 2015;Malin and Littlejohn, 2012a;Martínez et al, 2011;Newton-Howes et al, 2015;Seto et al, 2019), although mixed findings have been reported in this regard (Gonzalez et al, 2021). An association of harm-avoidance with deficient pain modulation has also been documented (Nahman-Averbuch et al, 2016).…”
Section: Temperament and The 'Big Five'mentioning
confidence: 84%
See 1 more Smart Citation
“…These observations are relevant in view of the literature linking neuroticism to severe FM symptoms (including pain), pain-related catastrophizing and pain-related anxiety, and worse clinical and healthrelated outcomes (Bucourt et al, 2017;Kadimpati et al, 2015;Malin and Littlejohn, 2012a;Martínez et al, 2011;Newton-Howes et al, 2015;Seto et al, 2019), although mixed findings have been reported in this regard (Gonzalez et al, 2021). An association of harm-avoidance with deficient pain modulation has also been documented (Nahman-Averbuch et al, 2016).…”
Section: Temperament and The 'Big Five'mentioning
confidence: 84%
“…Other pathological personality traits, such as hypochondriasis, depression, hysteria (e.g., somatization proneness), and schizophreniaspectrum features (e.g., unusual beliefs) as assessed by the Minnesota Multiphasic Personality Inventory-2 (MMPI-2), have been reported in FM (Gonzalez et al, 2021). It has been argued, however, that higher "schizophrenia" scores in the MMPI-2 in chronic pain populations are more related to the reported clinical manifestations (i.e., somatic and depressive-like symptoms) and disease impact than to the presence of serious mental illness (Moore et al, 1988).…”
Section: Other Personality Traitsmentioning
confidence: 99%
“…For example, Torres et al (2013) via the NEO Five-Factor Inventory identified two clusters, one of them showed higher neuroticism and lower extraversion and worse pretreatment clinical state including more psychosocial problems, and the other presented better adaptation. Similarly, Gonzalez et al (2020) using the Minnesota Multiphasic Personality Inventory-2 found two groups, one of them characterized by higher negative emotionality and introversion, presented a more disturbed profile in terms of general maladjustment, symptomatic behavior and clinical problem areas.…”
mentioning
confidence: 93%
“…They found that a low anxiety score and low grade of acceptance favour a resilient phenotype characterized by better coping [15]. A study by Gonzalez et al [16] could divide a cohort of FM patients (n=56) into two different clusters according to their personality and psychopathology features, but could not associate the clusters with health related phenotypes. Another study only performed the cluster analysis on a FM cohort (n=131) to identify difference in anxiety, depression, pain perception, and social comparisons [17].…”
Section: Introductionmentioning
confidence: 98%